Pengaruh Wounded inner child terhadap Kualitas Hubungan Romantis pada Dewasa Awal - Afifah Eka Puspita; Putri Dian Dia Conia; Meilla Dwi Nurmala (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
This study aims to identify the influence of wounded inner child on the quality of romantic relationships in early adulthood, as well as to explain the emotional and behavioral problems that arise due to wounded inner child in romantic relationships. The study used a quantitative approach with a correlational method. The research sample consisted of 173 students of the Guidance and Counseling Study Program, Sultan Ageng Tirtayasa University, class of 2024 and 2025 who were currently or had been in romantic relationships, and were selected using a purposive sampling technique. Data were collected through the wounded inner child scale and the romantic relationship quality scale, then analyzed using the Spearman Rank correlation test with the help of IBM SPSS Statistics. The results showed that wounded inner child has a significant influence with a negative direction on the quality of romantic relationships with a correlation coefficient value of -0.542 and Sig. 0.000 (p <0.05). These results indicate that the higher the level of wounded inner child an individual has, the lower the quality of romantic relationships they experience. Analysis of each aspect of the wounded inner child shows that all aspects have a significant influence on the quality of romantic relationships, the negative belief aspect being the most dominant with a correlation coefficient value of -0.516 and a contribution percentage of 26.63%. In addition, the wounded inner child is related to the emergence of various emotional and behavioral problems in romantic relationships, such as feelings of insecurity, fear of rejection, difficulty trusting partners, and obstacles in building communication and emotional closeness. Based on the results of the study, it can be concluded that the wounded inner child has a significant influence in a negative direction on the quality of romantic relationships in early adulthood